Ação da nicotina na indução da expressão dos genes PIK3CA, AKT1, HIF-1α, GLUT1 e CA9 em linhagens celulares SCC9 e DOK - Santos, Joaquim Gasparini dos (2021)
Nicotine is the main component present in tobacco products capable of activating pathways linked to tumorigenesis, tumor growth, metabolic changes and therapeutic resistance in several types of cancer, mainly in oral cavity cancer, but little is known about the effects of nicotine on lesions with malignant potential present in the oral cavity. In this work we seek to understand the effects of nicotine on the expression of genes linked to the pathway of tumor progression, such as PIK3CA, AKT1, HIF-1α, GLUT1 and CA9, in cell lines of DOK and SCC9. For that, the cell lines were submitted to cell viability assay by SRB, migration by wound test and analysis by RT-qPCR for expression of the genes of interest. Nicotine demonstrated the ability to increase the cell viability of SCC9 in all concentrations and in the time of 8 hours in relation to the control, the same was not observed in the wound test. In DOK cells, only the concentration of 10 µM, in the time of 8 hours, was able to increase the cellular migration in relation to the control. The ability of nicotine to increase gene expression in SCC9 was more evident at 24 hours and only the PIK3CA gene had a higher expression at 8 hours. In DOK it can be seen that the expression of the genes in question was restricted to the time of 8 hours and the concentration of 10 µM. Therefore, there is a relationship between exposure to nicotine and increased expression of genes in the SCC9 and DOK strains, to which the use of products with high concentrations of nicotine may contribute to the increased risk of malignization in regions with lesions with malignant potential present in the oral cavity.